The effect of inhaling concentrated oxygen between short-term anaerobic exercise - Suchy, J.; Heller, J.; Vodicka, P. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The performance benefits in sport of using concentrated O2 are inconclusive in the literature. In this context we examined whether inhaling 99.5% O2 would influence recovery between repeated shortterm anaerobic exercise. Methods Subjects attended two test sessions during one week, where each session included two Wingate tests. Between tests they inhaled Oxyfit or a placebo in a random order, at a frequency recommended by the manufacturer (Linde gas a.s.). Bottles of Oxyfit included 99.5 % O2. T The placebo bottle was of identical appearance but filled with air. During monitoring neither the research subjects or researcher staff knew whether Oxyfit or the placebo was being inhaled. For the test a Monark ergometer was used, calibrated for performance of up to 1 500 W, with a frequency of 50-160 rpm. Before the test subjects were informed of the need to work with maximum exertion from the start, and that during the test they could not use any strategies to distribute their strength. The tests were preceded by a five-minute warmup session. In the Wingate test a resistance of 6 W/kg was used. There were no restrictions on pedalling techniques (Heller at al., 1998). Results / Discussion The results show that inhaling 99.5% O2 positively influences the short-term recovery process in the given structure and the course of recovery depends on the intensity and duration of exercise, which was different in our test than in other models (Robbins et al., 1992; Yamaji et al., 1985), where no positive effect of inhaling O2 on recovery was demonstrated. The results revealed a significant difference between inhaling Oxyfit and the placebo on recovery before the second exercise, in favour of Oxyfit. A question remains concerning for how long Oxyfit works. According to ours and previous findings it is a matter of tens of seconds, up to one minute. The reason is the limited capacity of the tissues to use a non-physiologically increased amount of oxygen. In keeping with the importer`s instructions, the number of inhalations (using a mask to release a special valve) from the bottle for one application was eight. The reasons why the importer specifies eight inhalations for one application were not known. We were unable to accurately quantify the duration of individual inhalations. As the results of this pilot study may have wider impacts for sports, further testing for the use of Oxyfit on a broader sample of research subjects is recommended. It would also be appropriate to look at other methods and procedures relating to options for the application and use of Oxyfit.